Correlation of voice and quality of life with adjuvant radiotherapy in patients with larynx cancer - Medine Kara; Hülya Ertekin; Başak Şahin; Sibel Cevizci; Fevzi Sefa Dereköy (SERNEV, 2017)
Introduction: To evaluate theeffect of surgery type and adjuvant radiotherapy (RT) on voice quality andquality of life in patients with larynx cancer.Methods: 38 patients withlarynx cancer (37 males, 1 female; mean age 63.6 ± 9.63 years) were included inthis study. The parameters including tumor localization, TNM staging, and typeof surgery performed, adjuvant/primary RT intake and recurrence were recorded.All participants filled voice handicap index (VHI-10) and University of WashingtonQuality of Life Questionnaire version-IV (UWQOL-4). Voice analysis wasperformed by Xion Endo Strop-DX system. Questionnaire scores and voiceparameters were compared between groups.Results: There was astatistically significant low mean values of VHI detected within the group ofstripping/cordectomy compared to groups of partial or total laryngectomy. Inthe group without RT, the mean values of SPLmin, MPT, pain, appearance,swallowing and chewing subgroups of UWQOL scale were higher than the group treatedwith RT. There was a negative correlation identified between VHI and QOLparameters.Conclusion: In advanced stagelarynx cancer, increased surgical manipulation and adjuvant RT requirementsdecrease QOL. As a result early diagnosis of disease and treatment is veryimportant. As subjective voice quality increases QOL scores rise, indicatingthe importance of referring patients for voice therapy and psychotherapy aftertreatment.